2017
DOI: 10.1139/cjz-2016-0305
|View full text |Cite
|
Sign up to set email alerts
|

Island tameness and the repeatability of flight initiation distance in a large herbivore

Abstract: Antipredator behaviours can be lost relatively quickly in populations that are relieved of predation, as is known for several species inhabiting islands. Flight initiation distance (FID) is often studied in the context of island tameness; however, little is known about the factors that influence and maintain FID variation in predation-free populations. Here, we studied FID in foals of an isolated predator-free population of feral horses (Equus caballus L., 1758) on Sable Island, Canada, to determine if FID cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…The moderate within-individual repeatability of FID (r = 0.400) leaves room for differential selective disappearance of individuals depending on risk-taking propensity, but also for individually flexible adjustments of anti-predator behaviours according to internal state and environmental conditions. The repeatability of FID is at the lower end of published estimates, typically ranging from 0.34 to 0.88 [22][23][24][25][26], and lower than the one previously reported for eiders over a shorter portion of the species' lifespan [50], probably reflecting the fact that repeatability tends to decline with time between samplings [75].…”
Section: (A) Population-level Temporal Trends In Focal Variablesmentioning
confidence: 89%
“…The moderate within-individual repeatability of FID (r = 0.400) leaves room for differential selective disappearance of individuals depending on risk-taking propensity, but also for individually flexible adjustments of anti-predator behaviours according to internal state and environmental conditions. The repeatability of FID is at the lower end of published estimates, typically ranging from 0.34 to 0.88 [22][23][24][25][26], and lower than the one previously reported for eiders over a shorter portion of the species' lifespan [50], probably reflecting the fact that repeatability tends to decline with time between samplings [75].…”
Section: (A) Population-level Temporal Trends In Focal Variablesmentioning
confidence: 89%
“…longer FID) could also result from other life-history traits that we did not consider or the personality of the focal individual. Personality can affect FID in several ways [ 58 61 ], thus it is possible that within cities, birds that inhabit less human-intervened sites are less bold than the ones that live in fully urban zones and exhibited larger escape responses [ 62 ]. Moreover, birds in parks exhibited a similar response to the birds found in residential areas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that individuals might habituate to a behavioral assay when measured successively, which could enable the individual to become desensitized to the approach or, in contrast, become more responsive to the assay (Martin & Reale, 2008). A study on Sable Island horses (Equus caballus), found that repeatability of FID was high among individuals when tested on the same day, but decreased along trial days (Cabrera et al, 2017). I did not measure repeatability within days, but habituation across days could explain our results of low repeatability of FID.…”
Section: Discussionmentioning
confidence: 99%